The Hiawatha story - Scribbins, Jim (Fesler-Lampert Minnesota heritage book series., 2007)
Loved for their radically new, streamlined look, the Hiawathas Art Deco engines were a hallmark of American industrial design. For Midwestern passengers from Chicago to Aberdeen, the Hiawatha represented speed, comfort, and luxury. From 1935 to 1970 it carried countless passengers and even more memories. Richly illustrated, The Hiawatha Story brings the design and history of this beloved rail fleet to life.